2010
DOI: 10.1021/ja9098559
|View full text |Cite
|
Sign up to set email alerts
|

A Rare Example of a Krypton Difluoride Coordination Compound: [BrOF2][AsF6]·2KrF2

Abstract: The synthesis of [BrOF(2)][AsF(6)] x 2 KrF(2), its structural characterization, and bonding are described in this study. Although several KrF(2) adducts with transition metal centers have been previously reported, none have been crystallographically characterized. The solid-state Raman spectrum of [BrOF(2)][AsF(6)] x 2 KrF(2) has been assigned with the aid of quantum-chemical calculations. The low-temperature (-173 degrees C) X-ray crystal structure of [BrOF(2)][AsF(6)] x 2 KrF(2) consists of isolated molecula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
89
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

6
1

Authors

Journals

citations
Cited by 40 publications
(120 citation statements)
references
References 53 publications
27
89
0
1
Order By: Relevance
“…In contrast, the predicted factor-group splitting of the n 5 (A') band was observed for XeF 2 ·CrOF 4 (460/465cm À1 ), but not for KrF 2 ·CrOF 4 (486 cm À1 ). was observed at 254 cm À1 ,i n good agreement with its calculated value,2 50 cm À1 .T his band is shiftedt oh igher frequency relative to n 2 (P u )o ff ree KrF 2 (236 cm À1 ), [40] and is similart ot he in-phasea nd out-of-phase components of this coupled mode in [BrOF 2 ][AsF 6 ]·2KrF 2 (254/ 266 cm À1 ), [34] but occurs at lower frequency than in Mg(KrF 2 ) 4 (AsF 6 ) 2 (272/293 cm À1 ), [35] and [Hg(KrF 2 ) 8 ][AsF 6 ] 2 (262/ 282 cm À1 ). The experimental frequencies of n 5 (A')a nd n 15 (A") are lower and higher,r espectively,t han those of NgF 2 ·MoOF 4 (Kr,5 66/579 and 462/479 cm À1 ; Xe, 566/575 and 451/466 cm À1 ) [15] and NgF 2 ·WOF 4 (Kr,5 71/581 and 450/469cm À1 ;Xe, 573/577and 439/458 cm À1 ).…”
Section: Raman Spectroscopysupporting
confidence: 81%
See 2 more Smart Citations
“…In contrast, the predicted factor-group splitting of the n 5 (A') band was observed for XeF 2 ·CrOF 4 (460/465cm À1 ), but not for KrF 2 ·CrOF 4 (486 cm À1 ). was observed at 254 cm À1 ,i n good agreement with its calculated value,2 50 cm À1 .T his band is shiftedt oh igher frequency relative to n 2 (P u )o ff ree KrF 2 (236 cm À1 ), [40] and is similart ot he in-phasea nd out-of-phase components of this coupled mode in [BrOF 2 ][AsF 6 ]·2KrF 2 (254/ 266 cm À1 ), [34] but occurs at lower frequency than in Mg(KrF 2 ) 4 (AsF 6 ) 2 (272/293 cm À1 ), [35] and [Hg(KrF 2 ) 8 ][AsF 6 ] 2 (262/ 282 cm À1 ). The experimental frequencies of n 5 (A')a nd n 15 (A") are lower and higher,r espectively,t han those of NgF 2 ·MoOF 4 (Kr,5 66/579 and 462/479 cm À1 ; Xe, 566/575 and 451/466 cm À1 ) [15] and NgF 2 ·WOF 4 (Kr,5 71/581 and 450/469cm À1 ;Xe, 573/577and 439/458 cm À1 ).…”
Section: Raman Spectroscopysupporting
confidence: 81%
“…Their solid-state, near-staggered and eclipsed conformationsa re consequences of crystal packing and the small energy differences between these conformations. [34] Note that the NgÀF b bondso f NgF 2 ·CrOF 4 [Xe, (E) 2.035(3), (S) 2.057(2) ;K r, (NS) 1.9279(9) ] Table 1. [13] Similar trends are observedf or [BrOF 2 ] [AsF 6 ]·2NgF 2 [XeÀF t ,1 .956(5) ;X e ÀF b ,2 .053(4) [33] and KrÀF t , 1.847(4);K r ÀF b ,1 .933 (4) ].…”
Section: A-crof 4 and B-crofmentioning
confidence: 99%
See 1 more Smart Citation
“…(105,195). The only example presently known in which KrF 2 coordinates to a main-group center is [BrOF 2 ][AsF 6 ]Á2KrF 2 [1217521- and is the only coordination compound of KrF 2 that has been structurally characterized by x-ray crystallography (196).…”
Section: Krypton Compoundsmentioning
confidence: 99%
“…A considerable number of metal cations exhibiting this behavior towards XeF 2 have been synthesized and structurally characterized. Recent reviews outlining progress in this area [9,10] [20], Xe [21]) have been reported which contain NgF 2 molecules that are terminally coordinated to bromine(V) through fluorine. The Ng-F stretching frequencies of main-group cation complexes with NgF 2 show frequency shift patterns that are similar to those of the metal cation complexes (vide supra).…”
Section: Introductionmentioning
confidence: 99%